2018
DOI: 10.1007/s40259-018-0322-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety of Monoclonal Antibodies (Bevacizumab, Cetuximab, and Panitumumab) in Combination with Chemotherapy for Metastatic Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe last decade has seen the increasing use of biological medicines in combination with chemotherapy containing 5-fluorouracil/oxaliplatin or irinotecan for the treatment of metastatic colorectal cancer (mCRC). These combinations have resulted in increased progression-free survival (PFS) in patients with mCRC; however, there are remaining concerns over the extent of their effect on overall survival (OS). Published studies to date suggest no major differences between the three currently available mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 89 publications
2
26
0
1
Order By: Relevance
“…Consequently, countries can learn from each other. We also did not systematically review each paper for its quality using well-known scales such as the Newcastle-Ottawa scale or the Cochrane risk of bias tool as our emphasis was on contextualizing the findings rather than performing a systematic review for the reasons given (Marra et al, 2016;Ong et al, 2018;Almeida et al, 2018;da Silva et al, 2018;Saleem et al, 2019). In addition, we did not review each paper to assess whether the presence of diabetes, especially T2DM, had been defined according to WHO and other internationally recognized diagnostic criteria in view of the objectives of this paper (World Health Organisation, 2006;Manne-Goehler et al, 2019).…”
Section: Our Approachmentioning
confidence: 99%
“…Consequently, countries can learn from each other. We also did not systematically review each paper for its quality using well-known scales such as the Newcastle-Ottawa scale or the Cochrane risk of bias tool as our emphasis was on contextualizing the findings rather than performing a systematic review for the reasons given (Marra et al, 2016;Ong et al, 2018;Almeida et al, 2018;da Silva et al, 2018;Saleem et al, 2019). In addition, we did not review each paper to assess whether the presence of diabetes, especially T2DM, had been defined according to WHO and other internationally recognized diagnostic criteria in view of the objectives of this paper (World Health Organisation, 2006;Manne-Goehler et al, 2019).…”
Section: Our Approachmentioning
confidence: 99%
“…The current CRC rst-line treatment is bevacizumab combined with chemotherapy, such as 5-FU, oxaliplatin or irinotecan, the regimens evidently improve overall and progression-free survival in CRC patients. However, it worth to noted that in a meta-analysis review article, there are some statistically signi cant increase in severe adverse events associated with bevacizumab, for example, severe hypertension and gastrointestinal perforation [28]. In addition, Koichi Taira et al reported that patient received bevacizumab occurred skin ulcer and wound healing delayed, recommended the treatment of bevacizumab should be suspended at least 5 weeks before patient undergo an operation [29].…”
Section: Discussionmentioning
confidence: 99%
“…The current CRC rst-line treatment is bevacizumab combined with chemotherapy, such as 5-FU, oxaliplatin or irinotecan, the regimens evidently improve overall and progression-free survival in CRC patients. However, it worth to noted that in a meta-analysis review article, there are some statistically signi cant increase in severe adverse events associated with bevacizumab, for example, severe hypertension and gastrointestinal perforation [25]. In addition, Koichi Taira et al reported that patient received bevacizumab occurred skin ulcer and wound healing delayed, recommended the treatment of bevacizumab should be suspended at least 5 weeks before patient undergo an operation [26].…”
Section: Discussionmentioning
confidence: 99%